Inexperienced examiners and the Foot Posture Index: A reliability study. (December 2016) - McLaughlin, Patrick; Vaughan, Brett; Shanahan, James; Martin, Jake; Linger, Gabriel
Abstract: The Foot Posture Index (FPI-6) is a reliable (experienced examiners) assessment tool used in clinical practice to classify foot posture. No work has been completed to determine the reliability of the FPI-6 between novice examiners. Therefore, the aim was to determine the inter-examiner reliability of the FPI-6 using two novice examiners (graduate level osteopathy students). The FPI-6 was used to classify the feet of 83 students recruited as part of a larger study. Data were collected simultaneously by both examiners, but there was no communication between them. The scoring system provided by the FPI-6 manual was used to assess all feet. Collated data were assessed between examiners for reliability based on raw, transformed and foot type scores. The inter-examiner reliability was high for both left (intra-class correlation coefficient ICC2, 1 = 0.86) and right (ICC2, 1 = 0.85) feet for the novice examiners. When data were assessed based on foot type classification the examiners agreed on 76% of the left feet and 82% of the right feet with Kappa values of 0.73 and 0.72 respectively. The FPI-6 is a robust clinical tool that can be reliably utilised by inexperienced clinicians. Highlights: The FPI-6 is reliable when used by novice examiners. Experience, even limited, in musculoskeletal assessment is of benefit. The reliable use of the FPI-6 is not restricted to podiatrists.